ANALISIS PERAN MODAL SOSIAL DALAM PENGEMBANGAN AGRIBISNIS SAYURAN DATARAN TINGGI DI KABUPATEN GOWA - Halim, Hasriliandi; Suradi, Adam Rahman; Ramli, Fatmawati (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2024)
This research aims to analyze the role of social capital inupland vegetable farming development in Gowa Regency. Social capital isdefined as a set of values, norms, beliefs, and relationships that exist withina community that can help them achieve common goals. The researchmethod used is a qualitative method with a case study approach. Datacollection techniques were carried out through observation, interviews, andFocus Group Discussions (FGD) with upland vegetable farmers, farmergroups, and related institutions. The research results show that socialcapital plays an important role in the development of upland vegetablefarming in Gowa Regency. Strong social capital can encourage cooperationand coordination between farmers, farmer groups, and related institutionsin various aspects, such as providing infrastructure, training and extension,and marketing of agricultural products. Social capital can also encouragea spirit of mutual help and cooperation among community members inbuilding infrastructure, overcoming plant pests and diseases, and helpingfarmers who are experiencing difficulties. Trust and honesty that are builtwithin a community with strong social capital can also help to facilitatesales transactions, form savings and loan groups, and maintainenvironmental sustainability.